2019
DOI: 10.17116/oftalma201913505146
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of perifocal defocus spectacle lens correction in children with progressive myopia

Abstract: Периферическому дефокусу отводится значительная роль в формировании рефракции. Перифокальные очки позволяют дифференцированно произвести коррекцию центральной и периферической рефракции глаза по горизонтальному меридиану и исправляют или уменьшают периферическую гиперметропию. Цель исследования-изучить отдаленные результаты влияния ношения перифокальных очков на динамику рефракции у детей с прогрессирующей миопией. Материал и методы. Перифокальные очки назначали детям 7-14 лет с прогрессирующей миопией от (-)1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In the 15° zone, 100% of the eyes formed myopic defocus, which averaged −0.05 ± 0.1 D in temporal 15°, −0.25 ± 0.16 D in nasal 15°, and −0.44 ± 0.03 D in temporal 30°. In the nasal 30° zone, the hyperopic defocus decreased by four times and amounted to 0.38 ± 0.03 D. The rate of myopia progression decreased from 0.80 D of baseline values to 0.17 D at 4 to 5 years of follow-up [ 53 ].…”
Section: Optical Devices That Provide Peripheral Defocus and Their Ef...mentioning
confidence: 99%
“…In the 15° zone, 100% of the eyes formed myopic defocus, which averaged −0.05 ± 0.1 D in temporal 15°, −0.25 ± 0.16 D in nasal 15°, and −0.44 ± 0.03 D in temporal 30°. In the nasal 30° zone, the hyperopic defocus decreased by four times and amounted to 0.38 ± 0.03 D. The rate of myopia progression decreased from 0.80 D of baseline values to 0.17 D at 4 to 5 years of follow-up [ 53 ].…”
Section: Optical Devices That Provide Peripheral Defocus and Their Ef...mentioning
confidence: 99%
“…Tarutta et al (2019) described the long-term results of these perifocal defocus spectacle lenses in children between 7–14 years old with progressive myopia [ 13 ]. They studied the effect of these lenses on peripheral refraction at 15° and 30° in the nasal and temporal retina and showed a more negative peripheral refraction with perifocal lenses than the control for both nasal and temporal retina, even though in the 30° N the refraction was still positive [ 13 ]. These results are similar to the results obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of this lens was reported in a Russian-based study where the test group was 0.79 D less myopic than a control group after four years of follow-up. They found that the peripheral refraction was more myopic at the 15° nasal as well as 15° and 30° temporal zone [ 13 ]. Nevertheless, the actual effect of this lens on peripheral refraction and the potential impact on visual quality is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of progression of myopia decreased from 0.80D of baseline values to 0.17D at 4–5 years of follow-up. [ 47 ]…”
Section: Peripheral Defocus Ophthalmic Lensesmentioning
confidence: 99%